2016
DOI: 10.1016/j.bbmt.2016.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Molecular Remission before Allogeneic Stem Cell Transplantation in Adult Patients with Philadelphia Chromosome–Positive Acute Lymphoblastic Leukemia: Impact on Relapse and Long-Term Outcome

Abstract: Allogeneic stem cell transplantation (alloHSCT) in first complete remission (CR1) remains the consolidation therapy of choice in Philadelphia-positive (Ph+) acute lymphoblastic leukemia (ALL). The prognostic value of measurable levels of minimal residual disease (MRD) at time of conditioning is a matter of debate. We analyzed the predictive relevance of MRD levels before transplantation on the clinical outcome of Ph+ ALL patients treated with chemotherapy and imatinib in 2 consecutive prospective clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 30 publications
0
46
0
3
Order By: Relevance
“…For adults with relapsed or refractory (R/R) ALL, the long‐term prognosis has been poor, with allogeneic hematopoietic stem cell transplantation (HSCT) performed in patients in CR after salvage therapy as the only potentially curative approach . Patients with no measurable disease (ie, molecular or minimal residual disease [MRD] remission) prior to HSCT consistently fare better than those with MRD …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For adults with relapsed or refractory (R/R) ALL, the long‐term prognosis has been poor, with allogeneic hematopoietic stem cell transplantation (HSCT) performed in patients in CR after salvage therapy as the only potentially curative approach . Patients with no measurable disease (ie, molecular or minimal residual disease [MRD] remission) prior to HSCT consistently fare better than those with MRD …”
Section: Introductionmentioning
confidence: 99%
“…4 Patients with no measurable disease (ie, molecular or minimal residual disease [MRD] remission) prior to HSCT consistently fare better than those with MRD. [5][6][7][8] Blinatumomab, a bispecific T-cell-engaging (BiTE Ⓡ ) immuno-oncology therapy, redirects endogenous T-cells to cell surface antigen-expressing cancer cells (ie, CD19expressing B cells). After encouraging results obtained in phase 2 studies, [9][10][11][12] a phase 3 study (TOWER study) was conducted in 405 patients with R/R Philadelphia chromosome (Ph)-negative B-cell precursor ALL.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Development of the ability to detect minimal residual disease (MRD) far below the level of 5% blast cells has changed the landscape of risk stratification over the last decade. 11,[15][16][17] Several studies have shown that chemotherapy combined with TKI, which gives a higher complete remission (CR) rate and further MRD reduction, enables allogenic HSCT in a larger proportion of patients. 18 Despite the evident benefit of giving TKI before allogenic HSCT, available data regarding the post-transplant use of TKI are limited.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several retrospective studies have shown that MRD positivity measured prior to allogeneic hsct is also predictive relapse in adults with Ph+ ALL [3][4][5]. However, given that these have all been retrospective studies, patient populations, treatment strategies (including those with and without [6]. In this series, all patients were treated with a TKI (imatinib) plus chemotherapy, and then patients with a suitable donor underwent allogeneic hsct in CR1.…”
mentioning
confidence: 99%